STRATEGIC MANAGEMENT IN DEVELOPING AND IMPROVING THE QUALITY OF HOSPITAL HEALTH SERVICES - Lavia Al-Hazmy; Achmad Subahtiyar (LP2IHKI UMSurabaya, 2025)
Objective: This study aims to evaluate the role of strategic management in improving the quality of hospital health services through a systematic and planned approach. Methods: The approach used was a literature review of five scientific articles published between 2019-2024. Articles were selected based on inclusion criteria that included a focus on hospital services without interventions or comparisons, using either qualitative or quantitative methods. Results: The strategies found include strengthening the Hospital Management Information System (SIMRS), developing nursing human resources, optimizing the role of public relations, improving patient safety in inpatient rooms, and implementing patient safety in outpatient pharmacy services. Conclusion: Strategic management plays an important role in shaping a quality and sustainable hospital service system. The synergy between technology, human resources, and commitment to safety is key to improving service quality.